Synthesis of Zeolite Y from Lapindo Mud with the Comparative Variation of the Weight of NaOH/Mud and Molar SiO2/Al2O3 - Andarini, Novita; Haryati, Tanti; Suwardiyanto, Suwardiyanto; Sulistiyo, Yudi Aris (Indonesian Chimica Letters, 2022)
Lapindo mud is a waste that can be used as a zeolite formation material. Zeolite is a mineral there are silica and alumina. The zeolite synthesized was the zeolite Y. The synthesis of zeolite Y is carried out the melting method followed by hydrothermal process. The ratio of NaOH/sludge weight varied the weight of NaOH added to the sludge weight which was made constant, there were 1.1 gram of NaOH/1 gram of sludge; 1.3 gram of NaOH/1 gram of sludge; 1.5 gram of NaOH/1 gram of sludge; and 1.7 gram of NaOH/ 1 gram of sludge. The sludge was pretreated using HCl in the leaching process and NaOH for smelting. The melted sludge from the four variations was characterized using XRF. The results of characterization are used as the basis for determining the mass of SiO2 and NaOH that need to be added in the synthesis. The melted sludge was added with water, SiO2, and NaOH and cured for 48 hours at room temperature. The mixture that has been brooded is then filtered, the result of the filtering is the filtrate of sodium silicate and sodium aluminate solution. The filtrate was hydrothermal 100-105 °C for 24 hours. The resulting crystals were filtered and neutralized using aquademine. The resulting synthetic zeolite was white, then characterization was carried out using XRF and XRD. The characterization results on the variation of NaOH/sludge weight ratio could be seen from the XRF results. Zeolite Y varies the weight ratio of NaOH/sludge based on the character of the best zeolite produced at a weight ratio of NaOH/sludge 1.5.